Pediatric Autoimmune Neuropsychiatric Disorder Linked to Streptococcal Infections - Alqifari, Abdullah Nasser; Maxwell, Benjamin (Case Reports in Psychiatry, 2023)
Pediatric acute-onset neuropsychiatric syndrome (PANS) is a clinical condition with abrupt onset of obsessive–compulsive symptoms and/or severe eating restrictions and at least two concomitant cognitive, behavioral, or neurological symptoms. Pediatric autoimmune neuropsychiatric disorder associated with streptococcal infections (PANDAS) is a subtype of PANS with a controversial diagnosis. A case of a 12-year-old girl with severe eating restriction, obsessive–compulsive symptoms, anxiety, and neurological symptoms who initially was diagnosed with obsessive–compulsive disorder is presented. Published reports were reviewed for the evidence of diagnosis and treatment options of PANS/PANDAS. Studies show controversy regarding diagnosis. Moreover, study reports showed limited evidence for the treatment options. Selective serotonin reuptake inhibitors and psychotherapy are considered the main treatment with prompt infection treatment in the case of PANDAS.